On closure operators of Jonsson sets - Ulbrikht, O.I.; Urken, G.A. (Bulletin of the Karaganda University. Mathematics Series, 2024)
The work is related to the study of the model-theoretic properties of Jonsson theories, which, generally speaking, are not complete. In the article, on the Boolean of Jonsson subsets of the semantic model of some fixed Jonsson theory, the concept of the Jonsson closure operator Jcl was introduced, defining the J-pregeometry on these subsets, and some results were obtained describing this closure operator.
Keywords: Jonsson theory; semantic model; Jonsson set; closure operator; J-pregeometry